FAITH-BASED COUNSELING AS AN ALTERNATIVE TO RESTORING ADOLESCENT AFFECTION CONDITIONS AFTER EXPERIENCING PARENTAL DIVORCE - MUHAMMAD FERDIANSYAH; MUHAMMAD ZULFIKAR; AFFAN YUSRA; MUHAMMAD ALRIDHO LUBIS; FREDDI SARMAN; Muhammad Alridho Lubis (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2022)
The purpose of this study is to examine the picture of adolescent affection conditions after parents experience divorce. This type of research is qualitative research with a case study type.  Data collection techniques use interview observation instruments and documentation. Data is obtained through students, kindergarten teachers, homeroom teachers, subject teachers, parents, and peers. The validity test uses our criteria, namely (1) Trust test (2) Transferability test, (3) Dependability test, and (4) Conformity test. Furthermore, the data obtained during the process in the field is continuously analyzed which refers to the Miles and Huberman model. The results showed that the condition of adolescent affection subjects "XR"  (pseudonyms) after their parents experienced divorce was moody, had ex sive and sad disappointment expressed by crying, and withdrew from the social environment to make  "XR" behave negatively at school as evidenced by the appearance of skipping classes, decreased academic scores, irritability, and fighting friends at school so that it adversely affects his n development. Therefore, in this study, researchers recommend that faith-based counseling is the right alternative in dealing with e "XR" problem because in the service of a faith-based counseling model the counselor will focus on reducing the sense of security, calm through the disclosure, analysis, meaning appropriately and positively of the condition of the counselor's affection.